Relationship between family environment and emotional intelligence: examination of the moderating factor - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
Although a bulk of literature indicates that family environment influence emotional intelligence, the level of education as one of the important determinants which buffers this effect received little empirical attention. The current study investigated the moderating role of father’s education on the relationships between family environment and emotional intelligence among 234 early adolescents (girls and boys) in grades 2 and 3 of guidance schools of Tehran, Iran. Data were collected using the Emotional Quotient Inventory Youth Version (Bar- on EQ-i; YV, 2000) and the Moos and Moos Family Environment Scale. Results revealed that family environment fostered emotional intelligence in their early adolescents. Furthermore, the findings demonstrated that father’s education moderated the relationship between family environment and emotional intelligence. Specifically, early adolescents tended to indicate more emotional intelligence at higher levels of family environment when fathers have high level of education. These findings underscore the need for continued focus on the role of parent’s education when assessing the links between family environment and early adolescent’s emotional intelligence.